2018
DOI: 10.3329/brj.v21i1.37382
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of Jhum Rice (Oryza sativa L.) Landraces Collected from Rangamati District in Bangladesh

Abstract: Genetic diversity of 30 Jhum rice landraces was studied under irrigated condition through Mahalanobis D2 statistic for agro-morphological characters. The landraces were grouped into five clusters. The intercluster distances were higher than intra-cluster distances indicating wider genetic diversity among the landraces of different clusters. The intra-cluster distances were lower in all the cases reflecting homogeneity of the genotypes within the clusters. The principal component analysis exposed that the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
3
7
0
Order By: Relevance
“…The present study exhibited high variability in most of the observed qualitative traits of aromatic rice landraces. Similar types of work was also reported by other authors (Bisne and Sarawgi, 2008;Moukoumbi et al, 2011;Mau et al, 2017 andIslam et al, 2017). The unique and similar type aromatic landraces were found for different qualitative agro-morphological characters (Table 3) which could be used in hybridization programme regarding issues like distinctness of new variety and intellectual property rights.…”
Section: Qualitative Traits Characterizationsupporting
confidence: 85%
“…The present study exhibited high variability in most of the observed qualitative traits of aromatic rice landraces. Similar types of work was also reported by other authors (Bisne and Sarawgi, 2008;Moukoumbi et al, 2011;Mau et al, 2017 andIslam et al, 2017). The unique and similar type aromatic landraces were found for different qualitative agro-morphological characters (Table 3) which could be used in hybridization programme regarding issues like distinctness of new variety and intellectual property rights.…”
Section: Qualitative Traits Characterizationsupporting
confidence: 85%
“…Islam et al, (2014), Akter et al, (2016) and Ahmed et al (2010) reported six clusters each. Besides that, Islam et al (2017) and Siddique et al (2013) reported five clusters each in their experiment with rice genotypes. The distribution pattern revealed maximum number of genotypes in cluster IV (eight genotypes) followed by six genotypes in cluster I and four in cluster II, III and V.…”
Section: Variability and Diversity In Basmati Rice Genotypesmentioning
confidence: 95%
“…Moreover, knowledge of correlation between yield and its contributing agro-morphological traits are basic requirement to find out guidelines for plant selection. In rice, large amount of genetic variability has been reported (Khatun et al, 2015;Ahmed et al, 2015;Islam et al, 2017;Akter et al, 2018;Islam et al, 2018) which indicates the potential for genetic improvement. Partitioning of total correlation into direct and indirect effect by path analysis helps in making the selection more meaningful way.…”
Section: Introductionmentioning
confidence: 99%